Uji Aktivitas Ekstrak Etanol Daun Mimba (Azadirachta Indica A. Juss) Terhadap Bakteri Staphylococcus Aureus - Lovena, Tri Nova; Gulyla Hari, Dewi (As-Shiha: Jurnal Kesehatan, 2023)
Infectious disease is a disease caused by microorganisms which is the body's response due to immune stimulation. One of the herbal ingredients used as a therapeutic agent is neem (Azadirachta indica A.Juss). This study aims to determine the content of secondary metabolites, minimum inhibitory concentration (MIC) and antibacterial activity found in n-hexane and ethanol extracts of neem leaves to Staphylococcus aureus bacteria. The extraction method used is the maceration method, the MIC method used is the liquid dilution method and the antibacterial activity test uses the disc diffusion method. The results of the phytochemical screening showed that the simplicia, n-hexane and ethanol extract of neem leaves positively contained flavonoids, saponins, tannins, steroids/triterpenoids. The MIC test results on the ethanol extract was obtained at a concentration of 6.25%. The ethanol extract with a concentration of 7% has weak activity at a concentration of 14% and 21% has moderate activity.